2011
DOI: 10.3233/jad-2011-091717
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Aβ1-40 Peptide Increases Excitatory Neurotransmission and Induces Epileptiform Activity in Hippocampal Neurons

Abstract: Abstract. It is believed that amyloid-␤ peptide (A␤), in its aggregated-oligomeric state, constitutes one of the neurotoxic factors involved in the pathogenesis of Alzheimer's disease. With the objective of studying a potential role of the peptide on synaptic transmission, we studied the effect of soluble A␤ 1-40 on synaptic transmission in rat hippocampal neurons. Neurons incubated with 500 nM of A␤ 1-40 peptide for 3 days presented higher levels of intracellular calcium transients, as evaluated by fluorimetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 52 publications
3
20
0
Order By: Relevance
“…Administrations of soluble oAβ to cultured neurons (Cuevas et al, 2011), brain slices (Minkeviciene et al,, 2009; Varga et al,2014; Ren et al, 2014) or living animals (Orbán et al,2011; Busche et al, 2012) all induced significant hyperexcitability in hippocampal neurons. These findings are consistent with several AD mouse models in which elevated levels of Aβ are associated with altered neuronal activity, spontaneous seizures, and epileptiform discharges (Palop et al,2007; Brown et al, 2011; Kerrigan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Administrations of soluble oAβ to cultured neurons (Cuevas et al, 2011), brain slices (Minkeviciene et al,, 2009; Varga et al,2014; Ren et al, 2014) or living animals (Orbán et al,2011; Busche et al, 2012) all induced significant hyperexcitability in hippocampal neurons. These findings are consistent with several AD mouse models in which elevated levels of Aβ are associated with altered neuronal activity, spontaneous seizures, and epileptiform discharges (Palop et al,2007; Brown et al, 2011; Kerrigan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although patients with TLE present with a decline in cognition and memory tasks, there is no evidence of Aβ1‐42 oligomer deposition in hippocampus of these subjects. However, it was observed that the Aβ1‐40 soluble form induces epileptiform activity, thereby increasing glutamate excitotoxicity in hippocampal neurons . Thus we believe that reduced TOP activity may contribute to tissue excitability.…”
Section: Discussionmentioning
confidence: 89%
“…However, it was observed that the Ab1-40 soluble form induces epileptiform activity, thereby increasing glutamate excitotoxicity in hippocampal neurons. 6 Thus we believe that reduced TOP activity may contribute to tissue excitability. Because TOP acts as a kininase, destroying kinin-related and Ab peptides and MHC class I molecules, it may play a significant role in decreasing local inflammation and vasodilation.…”
Section: Discussionmentioning
confidence: 97%
“…The cellular mechanisms involved in Aβ‐induced disruption of neural network activity comprise changes in synaptic transmission (Balleza‐Tapia et al, ; Mura et al, ; Peña et al, ; Salamone et al, ; Satoh et al, ) and in intrinsic neuronal properties (Chen, ; Hou, Cui, Yu, & Zhang, ; Mondragón‐Rodríguez, Gu, et al, ; Peña et al, ; Rovira, Arbez, & Mariani, ; Shankar & Walsh, ; Ye, Selkoe, & Hartley, ), which involve direct actions of Aβ on ion channels (Balleza‐Tapia et al, ; Chen, ; Hou et al, ; Rovira et al, ; Shankar & Walsh, ; Ye et al, ) and/or their modulation through the activation of intracellular transduction pathways (Ekinci, Malik, & Shea, ; Wildburger & Laezza, ; Zhu et al, ). At the synaptic level, Aβ produces alterations at both presynaptic (Balleza‐Tapia et al, ; Cuevas et al, ; Dougherty, Wu, & Nichols, ; Nimmrich & Ebert, ; Peña et al, ; Ting, Kelley, Lambert, Cook, & Sullivan, ) and postsynaptic levels (Dinamarca, Ríos, & Inestrosa, ; Gylys et al, ; Harigaya, Shoji, Shirao, & Hirai, ; Hatanpaa, Isaacs, Shirao, Brady, & Rapoport, ; Ting et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with this proposal, transgenic AD animal models that overproduce Aβ exhibit spontaneous epileptiform seizures (Minkeviciene et al, ; Palop et al, ; Palop & Mucke, ; Verret et al, ; Ziyatdinova et al, ) and show a reduced threshold for convulsions (Del Vecchio, Gold, Novick, Wong, & Hyde, ). Although these data support the notion that Aβ influences epilepsy induction, there is scarce evidence that Aβ itself promotes the generation of epileptiform activity (Cuevas et al, ).…”
Section: Introductionmentioning
confidence: 99%